Distribution of oral carcinoma case requiring radiotherapy in the Oral and Maxillofacial Surgery Clinics - Jelita, Dinda Tegar; Riawan, Lucky; Hambali, Herman (Padjadjaran Journal of Dentistry, 2015)
Introduction: Carcinoma is a highly malignant tumour of epithelium that occurred in the oral cavity. One of the most common therapies given is radiotherapy, with healing, adjuvant, and palliative intentions. This research was aimed to discover the distribution of oral carcinoma requiring radiotherapy. Methods: This study was a retrospective, descriptive method. Samples were taken from the medical record of patients with oral cavity carcinoma requiring radiotherapy at the Oral and Maxillofacial Surgery Clinics of Hasan Sadikin Hospital, Bandung, of January 2006–December 2010. Results: This study indicated that as many as 23 (20.9%) cases of oral carcinoma requiring radiotherapy from a total of 110 oral carcinoma cases in that period. Type of radiotherapy most frequently found was adjuvant radiotherapy, by 14 (60.8%) cases. The most frequent type of oral carcinoma case requiring radiotherapy was squamous cell carcinoma, by 12 (52.1%) cases. Tongue become the most common area of oral carcinoma requiring radiotherapy, by 7 (30.4%) cases. Oral carcinoma case requiring radiotherapy was most frequently found in men by 14 (60.8%) cases. The age group of 41-50 was become the majority by 7 (30.4%) cases from all of the oral carcinoma case requiring radiotherapy. Conclusion: Distribution of oral carcinoma case requiring radiotherapy in the Oral and Maxillofacial Surgery Clinics of Hasan Sadikin Hospital is found in as many as 23 (20.9%) cases. Most frequent radiotherapy given is adjuvant radiotherapy (14 (60.8%) cases). The most frequent type of oral carcinoma case requiring radiotherapy is squamous cell carcinoma (12 (52.1%) cases). The most common area of oral carcinoma requiring radiotherapy is tongue (7 (30.4%) cases). Oral carcinoma case requiring radiotherapy was most frequently found in men (14 (60.8%) cases). The age group of 41-50 is the majority age suffered from disease (7 (30.4%) cases).